2019
DOI: 10.3847/1538-4357/ab1c5b
|View full text |Cite
|
Sign up to set email alerts
|

On the Elevation and Suppression of Star Formation within Galaxies

Abstract: To understand star formation in galaxies, we investigate the star formation rate (SFR) surface density (Σ SFR ) profiles for galaxies, based on a well-defined sample of 976 star-forming MaNGA galaxies. We find that the typical Σ SFR profiles within 1.5R e of normal SF galaxies can be well described by an exponential function for different stellar mass intervals, while the sSFR profile shows positive gradients, especially for more massive SF galaxies. This is due to the more pronounced central cores or bulges r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 125 publications
(210 reference statements)
9
72
0
Order By: Relevance
“…This further supports the idea that the narrow SFMS is indeed the result of the quasi-steady state between the inflow, outflow and star formation (e.g. Schaye et al 2010;Bouché et al 2010;Lilly et al 2013;Tacchella et al 2016;Wang et al 2019).…”
Section: The Radial Profiles Of Sfr79supporting
confidence: 82%
See 1 more Smart Citation
“…This further supports the idea that the narrow SFMS is indeed the result of the quasi-steady state between the inflow, outflow and star formation (e.g. Schaye et al 2010;Bouché et al 2010;Lilly et al 2013;Tacchella et al 2016;Wang et al 2019).…”
Section: The Radial Profiles Of Sfr79supporting
confidence: 82%
“…The dispersion of the SFR 5Myr /SFR 800Myr at a given relative galactic radius and a given stellar mass decreases with the (indirectly inferred) gas depletion time: locations with short gas depletion time appear to undergo bigger variations in their star-formation rates on Gyr or less timescales. In Wang et al (2019) we showed that the dispersion in star-formation rate surface densities Σ SFR in the galaxy population appears to be inversely correlated with the inferred gas depletion timescale and interpreted this in terms of the dynamical response of a gas-regulator system to changes in the gas inflow rate. In this paper, we can now prove directly with SFR 5Myr /SFR 800Myr that these effects are indeed due to genuine temporal variations in the SFR of individual galaxies on timescales between 10 7 and 10 9 years rather than possibly reflecting intrinsic, non-temporal, differences between different galaxies.…”
mentioning
confidence: 78%
“…Ellison et al 2018a;Hani et al 2020a). Wang et al (2019) find similar results with the same survey, but using the median SFR in stellar-mass bins (rather than the rSFMS) as reference. Morselli et al (2019) report similar bifurcations out to z = 1.2 using multiwavelength Hubble Space Telescope (HST) data selected from the GOODS+CANDELS campaign.…”
Section: Global Sfr Enhancement Versus Radial Structuresupporting
confidence: 71%
“…By definition, these mechanisms act gradually, thereby leaving a Q galaxy with roughly the same mass and size, and the same structure as the original SF galaxy. Most SF galaxies form in an inside-out fashion (Pezzulli et al 2015;Ellison et al 2018;Wang et al 2019), leading to negative age gradients. At the same time, chemical enrichment models predict negative or flat stellar metallicity gradients (with some inversion in the centre, see Schönrich & McMillan 2017).…”
Section: Discussionmentioning
confidence: 99%